New Zealand : Selected Issues. (IMF Staff Country Reports; Country Report, 2003)
This Selected Issues paper examines the external linkages of the New Zealand economy. Empirical results from vector autoregressive models suggest that economic activity in Australia tends to have more of a significant direct impact on New Zealand than does activity in the United States. Fluctuations in the U.S. GDP, however, appear to be transmitted to New Zealand indirectly through their effects on the Australian economy. Financial linkages also have been important components in transmitting shocks from Australia and the United States to the New Zealand economy.